Fever of unknown origin in children: the experience of one center in Turkey - Tezer, Hasan; Ceyhan, Mehmet; Kara, Ateş; Cengiz, Ali Bülent; Devrim, İlker and Seçmeer, Gülten (The Turkish Journal of Pediatrics, 2012)
Knowledge about the etiology of fever of unknown origin (FUO) has been changed under the influence of new advances in diagnostic techniques in both adulthood and childhood. Seventy-seven patients with the diagnosis of FUO were evaluated retrospectively. Forty-six (60%) of the patients were male and 31 (40%) were female, with ages ranging from 4 months to 16 years (mean: 4.5 years). Physical findings were absolutely normal in 33 (42.9%) patients, and the most common findings were hepatosplenomegaly (15.5%) and lymphadenopathy (15.5%). The etiologies were determined in 69 patients with FUO. The most common diagnoses were infectious diseases (50.7%), malignancy (14.4%), collagen vascular disorders (7.2%), and miscellaneous conditions (27.5%). With the development of diagnostic tools, the etiologies in a considerable number of patients with FUO were diagnosed. A detailed history and physical examination are required for accurate diagnosis, and if indicated, invasive procedures should be instituted.